2016
DOI: 10.17265/2159-581x/2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of Agroindustrial Residues of Coffee, Sugarcane Straw and Coconut-Fibers in a Semi-pilot Plant for Production of Bio-oils: Gas Chromatographic Characterization

Abstract: Microbial, vegetal or animal organic matter, which has potential to be transformed into energy, is considered biomass. Among the various alternative energy sources, biomass is the only one with the possibility of generating a class of substances of interest for fine chemistry (ketones, aldehydes, alcohols, phenols, etc.). From biomass, it is possible to produce bio-oil using pyrolysis, a thermodegradation process. The quality of the bio-oil depends on the process conditions (pyrolysis temperature, heating temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…Machado et al [200] noted that both the bagasse and leaves of sugarcane have potential to be used as substrates to obtain high value-added products from their cellulosic fractions, such as organic acids, biofuels, and biopolymers. Bispo et al [203] produced bio-oil through pyrolysis of sugarcane straw. Simo et al [204] investigated anaerobic digestion of sugarcane bagasse to produce biogas while Patil and Deshannavar [205] investigated the potential of using sugarcane leaves for producing briquettes.…”
Section: Soybeanmentioning
confidence: 99%
“…Machado et al [200] noted that both the bagasse and leaves of sugarcane have potential to be used as substrates to obtain high value-added products from their cellulosic fractions, such as organic acids, biofuels, and biopolymers. Bispo et al [203] produced bio-oil through pyrolysis of sugarcane straw. Simo et al [204] investigated anaerobic digestion of sugarcane bagasse to produce biogas while Patil and Deshannavar [205] investigated the potential of using sugarcane leaves for producing briquettes.…”
Section: Soybeanmentioning
confidence: 99%
“…It is found that the phenols are major in both area (approximately 80%) and in number (44.90% of the identified compounds). This fact occurs due to the high content of lignin present in the biomass used (MIGLIORINI et al, 2013;ZHANG et al, 2013;BISPO et al, 2016). According to Souza, et al (2012), woody materials such as peach stone are rich in lignin and cellulose and when carbonized, they are thermally degraded in ketones, alcohols, furan derivatives and phenolic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…From this last step, the ideal pyrolysis temperature was determined to obtain better bio-oil yields. Therefore, the maximum temperature selected to carry out pyrolysis in this study was set at 700°C, aligned with findings in the literature on green coconut fiber pyrolysis (Almeida et al 2013;Bispo et al, 2016).…”
Section: Biomass Characterizationmentioning
confidence: 89%